Outcomes of Non-anesthesiologist-Administered Propofol in Pediatric Gastroenterology Procedures - Lee, Frances C.; Queliza, Karen; Chumpitazi, Bruno P.; Rogers, Amber P.; Seipel, Catherine; Fishman, Douglas S. (Frontiers in Pediatrics, 2021)
Background: Pediatric data on non-anesthesiologist administered propofol (NAAP) in endoscopy is limited. Our aim was to examine the safety and efficacy of NAAP provided by pediatric hospitalists in pediatric endoscopy. Methods: We retrospectively reviewed 929 esophagogastroduodenoscopy (EGD), colonoscopy, and EGD/colonoscopy cases in children aged 5-20 years between April 2015 and December 2016 at a large children's hospital. We analyzed the data for adverse events in relation to demographics and anthropometrics, American Society of Anesthesiologists physical classification score, presence of a trainee, co-morbid conditions, and procedure time. Results: A total of 929 cases were included of which 496 (53%) were completed with NAAP. Seventeen (3.4%) NAAP cases had an adverse event including: 12 cases of hypoxia, 2 cardiac, and 3 gastrointestinal adverse events. General anesthesia cases had 62 (14.3%) adverse events including: 54 cases of hypoxia, 1 cardiac, 7 gastrointestinal, and 1 urologic adverse event. No adverse events in either group required major resuscitation. NAAP vs. general anesthesia had a lower overall adverse event rate (3.4% vs. 14.3%, p < 0.0004) and respiratory adverse event rate (2.4% vs. 12.5%, p < 0.0004). Overall cardiac and gastrointestinal adverse event rates were comparable. When accounting for all captured factors via logistic regression both younger age (P<0.001) and general anesthesia (P<0.0001) remained risk factors for an adverse event. Conclusion: The overall adverse event rate of NAAP was low (3.4%) with none requiring major resuscitation or hospitalization, comparable to adult studies, and suggests that NAAP provided by pediatric hospitalists has an acceptable safety profile.